1999
DOI: 10.1111/j.1745-4557.1999.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Filleted Salmon in Various Retail Packages

Abstract: The quality attributes of salmon filleted and retail packed directly afier slaughtering or ajier transport in various bulk packages were observed during storage at +2C. The retail packages used were overwrap, vacuum and gas packages (40% CO, + 60% h$ or 60% CO, + 40% Nj. Microbial growth was clearly greater in overwrapped and slightly greater in vacuum packed samples than in gas packed samples. The diflerences were more evident when the fillets were directly retail packed without preceding bulk transport. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 8 publications
7
42
2
1
Order By: Relevance
“…Dalgaard et al 20 reported increased liquid loss with increasing CO 2 concentrations for MA-packaged cod (48-100% CO 2 ), as confi rmed for MA-packed salmon (2 and 1.5% for 60 and 40% CO 2 , respectively). 15 In the present study, all the samples in 280 ml trays had similar levels of liquid loss despite different levels of CO 2 in the headspace. The samples in the 1800 ml trays had signifi cantly lower liquid loss compared with the 280 ml trays (Figure 3).…”
Section: Liquid Lossmentioning
confidence: 71%
“…Dalgaard et al 20 reported increased liquid loss with increasing CO 2 concentrations for MA-packaged cod (48-100% CO 2 ), as confi rmed for MA-packed salmon (2 and 1.5% for 60 and 40% CO 2 , respectively). 15 In the present study, all the samples in 280 ml trays had similar levels of liquid loss despite different levels of CO 2 in the headspace. The samples in the 1800 ml trays had signifi cantly lower liquid loss compared with the 280 ml trays (Figure 3).…”
Section: Liquid Lossmentioning
confidence: 71%
“…It has been reported that dissolved CO 2 in the products would decrease the waterholding capacity. 34 However, a significant effect was not found for salmon, 5 with a typical drip loss around 2% under 60% CO 2 atmospheres, compared to about 0.5% in air storage. For wolf-fish we found that the drip loss in MA-stored products at −1°C was about 2% higher than in air and that the…”
Section: Drip Lossmentioning
confidence: 85%
“…4 Gas composition (%) in headspace of modified atmosphere packaged wolf-fish. 5 Drip loss formed in package expressed as percentage of initial fish weight. 6 Scores from sensory evaluation.…”
Section: (A-d) Sensory Microbiological and Chemical Analysis On Packmentioning
confidence: 99%
See 1 more Smart Citation
“…5,10,14±16 Randell and co-workers 17,18 reported a combination of bulk storage of whole salmon followed by packaging of ®llets of the same ®sh in retail packages. This combination of storage methods using adjusted atmospheres should increase the shelf-life of chilled whole gutted hake as well.…”
Section: ±11mentioning
confidence: 97%